A comparison of diameter distribution models for Khaya ivorensis A.Chev. plantations in Brazil. Issue 4 (2nd October 2018) - Mayrinck, Rafaella Carvalho; Filho, Antonio Carlos Ferraz; Ribeiro, Andressa; Oliveira, Ximena Mendes de; Lima, Renato Ribeiro de
Abstract : The purpose of this study was to compare Beta, Gamma, Johnson's S B and Weibull functions fitted by different methods for describing the horizontal structure of Khaya ivorensis (African mahogany) plantations in Brazil. The database comprised 128 plots from six plantations at varying ages. The function fits were compared using the Kolmogoroff–Smirnoff test, mean bias and mean absolute error for the number of trees and basal area per hectare per diameter class. Johnson's S B outperformed the other functions, although all functions provided an adequate fit. The best methods were method of moments and maximum likelihood fitted using 25% of the minimum observed diameter as the location parameter for the Johnson's S B function. The errors were greater in diameter classes with higher frequencies. Location and scale parameters were highly correlated with mean diameter and age for the Weibull and Johnson's S B functions, respectively, which is convenient for diameter prediction. Gamma's scale parameter had medium correlation with age. Beta's parameters had low correlation with stand attributes assessed.